A geographical approach to identify phosphorus-efficient genotypes among landraces and wild ancestors of common bean - Beebe, Stephen E.; Lynch, J; Galwey, Nicholas W.; Tohme, Joseph M.; Ochoa, Iván E. (Springer, 1997)
Cultivars of common bean (Phaseolus vulgaris L.) capable of yielding well at low levels of native or added phosphorus (P) are highly desirable in many tropical production systems. The objective of the present study was to identify geographical regions which might be sources of such genotypes. A total of 364 landraces, cultivars and wild genotypes, drawn from a broad geographic range, were divided on the basis of growth habit into four field trials, each comprising two levels of P, stressed and unstressed, on an infertile Andosol in Popayan, Colombia. The regression relationship between grain yield per plant in the presence and in the absence of stress was determined, and each genotype's deviation from this relationship was used as a measure of P-efficiency. There was highly significant variation in efficiency among genotypes in all growth habits, and in climbing beans there were consistent regional differences, superior genotypes being identified with greater frequency among those from Bolivia, West Mexico and South Mexico-West Guatemala. The latter region was promising for prostrate bush genotypes also. Wild beans in general performed relatively poorly; it appears that P-efficiency traits in P. vulgaris have been acquired during or after domestication. These results confirm that genetic differences in P-efficiency exist among common bean genotypes and suggest that these are related to geographic origin. Furthermore, the use of a representative sample of germplasm can help to identify segments of the gene bank that are especially promising as sources of desirable traits.